Can we reliably compare student engagement between universities? Evidence from the United Kingdom Engagement Survey. (4th May 2019) - Bokhove, Christian; Muijs, Daniel
ABSTRACT: Policy changes in the higher education landscape have given way to increased interest in the way students perceive engagement in UK higher education. This paper examines whether we can reliably distinguish between institutions and disciplines, and what key student and institutional variables are a predictor of engagement of undergraduate students. Using data from two waves of the United Kingdom Engagement Survey (UKES), a national survey of undergraduate student engagement, we constructed multilevel models for different aspects of student engagement. The results show that the vast majority of the variance of the models is at the student level, indicating that demographic characteristics seem to contribute most to differential aspects of engagement. Some variance at student level could be explained: females, distance learners, part-time students, and disabled student indicators were negative predictors of engagement, while indicators for Black and minority ethnic (BME) students and for students from Africa and Asia were positive predictors of engagement.